Assessment of the Impact of Boko-Haram Insurgency on Food Crop Production in Chibok Local Government Area of Borno State, Nigeria. (Global Journal of Human-Social Science, 2020)
Boko Haram Insurgency has affected the livelihood of rural households in the North-Eastern region of Nigeria. This research was carried out to assess the impact of insurgency on the food crop production in Chibok Local Government Area of Borno State, Nigeria. Data for this study were collected from 80 randomly sampled farmers in the study area. Simple descriptive statistics were used in analyzing the data. The study revealed that there was a considerable decline in the production capacities of the rural farmers in the area as a result of increased insurgent activities. It was therefore recommended that Government should prioritize ending insurgency in the area in order to sustain food production in Nigeria.
Keywords: boko haram; food crop; insurgency; livelihood; rural; production